2020
DOI: 10.1016/j.polgeo.2019.102073
|View full text |Cite
|
Sign up to set email alerts
|

Come rain, or come wells: How access to groundwater affects communal violence

Abstract: This paper empirically analyzes the relationship between groundwater scarcity and incidences of communal violence. Case studies suggest that appropriating water is more likely when resource scarcities are not effectively mitigated and where property rights are disputed. Yet, covering water more broadly remains piecemeal in quantitative research on communal conflict. While water scarcity features in large-N literature on climate variability and non-state conflicts, such studies rely heavily on rainfall data whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 95 publications
1
29
0
Order By: Relevance
“…One strain of research examines how water insecurity impacts international war and cooperation (Koubi et al, 2014; Mitchell & Zawahri, 2015), while other studies analyze some of its impacts on civil conflict (Selby & Hoffmann, 2014; Döring, 2020). For example, Döring (2020) recently analyzed the impact of access to groundwater on communal conflicts in Africa and the Middle East, and found that in these contexts water insecurity increases the risk of communal conflict. Water insecurity’s impact on social unrest, however, remains surprisingly less studied.…”
Section: Theoretical Argumentmentioning
confidence: 99%
See 2 more Smart Citations
“…One strain of research examines how water insecurity impacts international war and cooperation (Koubi et al, 2014; Mitchell & Zawahri, 2015), while other studies analyze some of its impacts on civil conflict (Selby & Hoffmann, 2014; Döring, 2020). For example, Döring (2020) recently analyzed the impact of access to groundwater on communal conflicts in Africa and the Middle East, and found that in these contexts water insecurity increases the risk of communal conflict. Water insecurity’s impact on social unrest, however, remains surprisingly less studied.…”
Section: Theoretical Argumentmentioning
confidence: 99%
“…Like food insecurity, water insecurity can be caused by natural factors (e.g. droughts, heatwaves), human behaviors (misappropriation or contamination of water resources), and population dynamics (Bakker, 2012; Hoekstra, Buurman & van Ginkel, 2018; Döring, 2020). Bakker (2012), for instance, identifies four individual pathways of water insecurity’s impact: (i) drinking water supply, for example by disconnecting individuals from access to water, (ii) economic growth, for example by contracting the agricultural sector, (iii) threats to ecosystems, and (iv) increased variability due to climate change, which requires more effective means of local and state-level resource governance.…”
Section: Theoretical Argumentmentioning
confidence: 99%
See 1 more Smart Citation
“…Any evidence that environmental factors led to Syria’s civil war falls in line with research that found temperature extremes (Burke et al, 2009; Hsiang, Burke & Miguel, 2013; Maystadt, Calderone & You, 2015; van Weezel, 2020) and rainfall deficits (Fjelde & von Uexkull, 2012; Hendrix & Salehyan, 2012; Maystadt & Ecker, 2014; Raleigh, Choi & Kniveton, 2015; von Uexkull et al, 2016; Harari & La Ferrara, 2018; van Weezel, 2019; Döring, 2020) elevate armed conflict risk. Weather trends will become increasingly unpredictable as climatic change continues (Giorgi, 2006; Dai, 2013) and this could have impacts on crop productivity that lead to violence (Vesco et al, 2021).…”
Section: Introductionmentioning
confidence: 55%
“…We believe that dry conditions could elevate the risk of conflict as a result of harmful livelihood losses that follow droughts (Vestby, 2019; Buhaug et al, 2020). Existing research similarly found that rainfall deficits were associated with conflict in Indonesia when irrigation is lacking (Gatti, Baylis & Crost, 2020), violence across Africa when agricultural shortages raised the price of food in local markets (Raleigh, Choi & Kniveton, 2015), and communal attacks when groundwater supplies are insufficient (Döring, 2020).…”
Section: Discussionmentioning
confidence: 99%